2013
DOI: 10.1007/s11552-013-9566-x
|View full text |Cite
|
Sign up to set email alerts
|

Carpal Tunnel Release Using the Paine Retinaculotome Inserted through a Palmar Incision

Abstract: After many years, no permanent nerve or vascular damage has been reported. This method has demonstrated itself to be efficient and safe in the treatment of the carpal tunnel syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 14 publications
0
18
0
3
Order By: Relevance
“…A steep learning curve 10,45 increased the technical difficulties, 13,21,28,32,33,50 and potentially devastating complications have been reported with endoscopic techniques. 1,5,13,18,21,27,28,51 A variety of limited-open or mini-open techniques using multiple devices, 4,26,[52][53][54][55] or no special devices, [56][57][58][59] have not yet undergone the intense scrutiny given to more established endoscopic carpal tunnel-release techniques, and that complications and learning curves associated with these techniques should be studied further before they are put to wider use. 10 In the present article, a new technique for carpal tunnel release is reported for the first time in a peer reviewed journal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A steep learning curve 10,45 increased the technical difficulties, 13,21,28,32,33,50 and potentially devastating complications have been reported with endoscopic techniques. 1,5,13,18,21,27,28,51 A variety of limited-open or mini-open techniques using multiple devices, 4,26,[52][53][54][55] or no special devices, [56][57][58][59] have not yet undergone the intense scrutiny given to more established endoscopic carpal tunnel-release techniques, and that complications and learning curves associated with these techniques should be studied further before they are put to wider use. 10 In the present article, a new technique for carpal tunnel release is reported for the first time in a peer reviewed journal.…”
Section: Discussionmentioning
confidence: 99%
“…A tourniquet was applied to the arm and inflated to 250 mmHg. 4,27 Surgical loupes (3 Â magnification) were used for the procedure. One goal of this technique is to avoid any type of palm incision, thus, a transverse incision was made over the palmar distal wrist crease, starting at a couple of mm radial to the medial border of the palmaris longus tendon 32 and extending toward the ulna by 1 cm 25 ( Figures 5 and 6), however, any other surgical approach may be used.…”
Section: Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Open field (Figures 1F and G) or endoscopy has a similar time out of work, but the latter MN damage is more frequent [52][53][54]. Retinaculotome decompression is similar to endoscopy but with less time and cost requirements [55] (Figures 1H and I). Re-operation is indicated in failure or recurrence.…”
Section: Carpal Tunnel Syndrome (Cts)mentioning
confidence: 99%
“…Attempting to avoid the side effects induced by intra-pelvic obturator nerve trunk resection, some researchers attempted local anesthetic agent infiltration at the obturator nerve outside the obturator canal and at the quadratus femoris nerve branch and reported that it also provided good short term pain relief [43,57,72,[75][76][77][78][79][80][81][82]. This pain improvement lasted usually one to four days [27,81] but in some exceptional cases up to three months [80,81].…”
Section: Historical Background Hip Joint Denervationmentioning
confidence: 99%